2013
DOI: 10.1007/s00213-013-3251-1
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant-like effects of topiramate alone or combined with 17β-estradiol in ovariectomized Wistar rats submitted to the forced swimming test

Abstract: Topiramate alone or combined with 17β-estradiol produced antidepressant-like actions; and 17β-estradiol shortened the onset of the antidepressant-like effects of topiramate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Several studies have reported that estrogen replacement therapy exerts antidepressive actions in females with depression in clinical studies, as well as females in animal models . Furthermore, estrogen can be combined with selective serotonin re‐uptake inhibitors (SSRIs), to produce additive antidepressant‐like effects . Curiously, fasting produces estrogenic effects even in ovariectomized mice, and caloric restriction increases expression of estrogen receptors (ERs) but not the expression of the androgen receptors in mouse ovaries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that estrogen replacement therapy exerts antidepressive actions in females with depression in clinical studies, as well as females in animal models . Furthermore, estrogen can be combined with selective serotonin re‐uptake inhibitors (SSRIs), to produce additive antidepressant‐like effects . Curiously, fasting produces estrogenic effects even in ovariectomized mice, and caloric restriction increases expression of estrogen receptors (ERs) but not the expression of the androgen receptors in mouse ovaries .…”
Section: Introductionmentioning
confidence: 99%
“…8,11 Furthermore, estrogen can be combined with selective serotonin re-uptake inhibitors (SSRIs), to produce additive antidepressant-like effects. 12,13 Curiously, fasting produces estrogenic effects even in ovariectomized mice, 14 and caloric restriction increases expression of estrogen receptors (ERs) but not the expression of the androgen receptors in mouse ovaries. 15 Therefore, this study investigated the antidepressant-like effects of acute fasting combined with estrogen treatment, and the potential mechanisms that might underlie these combined antidepressant effects.…”
mentioning
confidence: 99%
“…Intragastric administration of 1-MID in doses of 20, 40, and 80 mg/kg BW to chronic forced swim stress-induced depression model rats for 14 days obviously increased the body weight and sucrose preference via decreasing serum CORT and upregulating the expression of BDNF protein [123], suggesting that 1-MID is a promising lead compound of novel antidepressant that originated from OR, and further researches associated with lead optimization as well as structure-activity relationship will be needed to investigate. In terms of petroleum ether extract from OR, previous studies have reported that three compounds including cholesterol, cholestan-3,6-dione, and cholest-4-ene-3-one were separated from it [42], which belong to the steroids that elicit antidepressant-like activities [142144]; however, additional experiments will still be wanted to verify whether these compounds mainly contribute to the antidepressant effect of petroleum ether extract from OR.…”
Section: Biological Functions Of Oviductus Ranaementioning
confidence: 99%
“…On the other hand, it has been suggested that the use of a combined therapy, estradiol plus antidepressant, could be advantageous for the treatment of depression in perimenopausal or menopausal women (Vega-Rivera et al, 2016). Some clinical studies suggest that estrogen may enhance the effect of other antidepressants (Estrada-Camarena et al, 2004), such as selective serotonin reuptake inhibitors (SSRIs) (Benmansour et al, 2016b), agomelatine (El-Khatib et al, 2020), escitalopram (Ibrahim et al, 2016), fluoxetine (Récamier-Carballo et al, 2012), and topiramate (Molina-Hernández et al, 2014). However, other studies have reported that estradiol can block the antidepressant effect of some antidepressants such as sertraline, desipramine, or fluvoxamine (Shah and Frazer, 2014;Benmansour et al, 2016aBenmansour et al, , 2016b.…”
Section: Introductionmentioning
confidence: 99%